Mucosal Applications of Poloxamer 407-Based Hydrogels: An Overview - Elena Giuliano; Donatella Paolino; Massimo Fresta; Donato Cosco (MDPI AG, 2018)
Poloxamer 407, also known by the trademark Pluronic® F127, is a water-soluble, non-ionic triblock copolymer that is made up of a hydrophobic residue of polyoxypropylene (POP) between the two hydrophilic units of polyoxyethylene (POE). Poloxamer 407-based hydrogels exhibit an interesting reversible thermal characteristic. That is, they are liquid at room temperature, but they assume a gel form when administered at body temperature, which makes them attractive candidates as pharmaceutical drug carriers. These systems have been widely investigated in the development of mucoadhesive formulations because they do not irritate the mucosal membranes. Based on these mucoadhesive properties, a simple administration into a specific compartment should maintain the required drug concentration in situ for a prolonged period of time, decreasing the necessary dosages and side effects. Their main limitations are their modest mechanical strength and, notwithstanding their bioadhesive properties, their tendency to succumb to rapid elimination in physiological media. Various technological approaches have been investigated in the attempt to modulate these properties. This review focuses on the application of poloxamer 407-based hydrogels for mucosal drug delivery with particular attention being paid to the latest published works.